Geo-spatial variability in soil health of Biwan watershed located at Mewat district of Haryana, India - GURJAR, D S; SUDHISHRI, S; MISHRA, A K; KAUR, R; KHANNA, M (The Indian Journal of Agricultural Sciences, 2018)
A study was carried out to evaluate the geo-spatial variability of soil health parameters in Biwan watershed located in the Mewat district of Haryana in 2012-13. The main objective of this study was to determine spatial variability of selected soil health parameters that influence crop growth and yield. Soil samples (100) with GPS co-ordinates were collected on random basis from Tapkan, Biwan, Shonkh, Palla and Palladi villages of Biwan watershed during pre-monsoon period (May 2012). Soil health parameters such as pH2, electrical conductivity (EC2), organic carbon,Â  available NPK and micronutrient (Zn, Fe, Cu and Mn) were analyzed from each sample by the standard methods. The spatial variability maps for different soil health parameters were prepared through GIS software (ArcGIS 9.0). Results indicated that the pH2 (6.0-8.59) and EC2 (